Review of Islamic Marriage Law and Gender Justice Towards SEMA Number 3 Of 2018 Concerning Rejection of Isbat Polygamy Cases in Religious Courts - Abdul Halim, Halmi (Journal of Family Law and Islamic Court, 2024)
Having more than one wife or polygamy in Indonesia is regulated in Law Number 1 of 1974 concerning Marriage. Marriages in Indonesia are also regulated in terms of registration. In society there is a phenomenon of husbands marrying more than one wife (polygamy) without being recorded by the Marriage Registrar. Because the legal status of the second, third or fourth wife is unclear if it is not recorded, an application for polygamous isbat is submitted to the court. However, there is SEMA regulation Number 3 of 2018 which prohibits polygamous isbat from being processed in court. Therefore, the aim of this research is to find answers to questions related to polygamous isbat procedures, analysis of Islamic marriage law regarding the rejection of polygamous isbat in religious courts and gender justice analysis regarding the rejection of polygamous isbat in religious courts. The research method used was content analysis, which used a data search method, namely literature study. From this research it was found that the marriage isbat procedure with polygamous isbat is different, the rejection of polygamous isbat in religious courts according to Islamic Marriage Law is not a new problem and the rejection of polygamous isbat in Religious Courts according to gender justice is divided into two versions, if viewed from the first wife's version it is fair gender, while for second or subsequent wives there is no gender equality.